Mental health and quality of life of patients undergoing hematopoietic stem cell transplantation (HSCT) prior to hospitalization: a cross-sectional complete state health study. Issue 1 (1st January 2021) - Corman, Maya; Rubio, Marie-Thérèse; Cabrespine, Aurélie; Brindel, Isabelle; Bay, Jacques-Olivier; Peffault De La Tour, Régis; Dambrun, Michaël
ABSTRACT: Objective: The main goal of this cross-sectional study was to examine the relationships between negative/positive psychological dispositions, mental health, and quality of life (QoL) prior to hospitalization among patients undergoing hematopoietic stem cell transplantation (HSCT). Method: A total of 187 patients ( Mage  = 52.07 years) completed a questionnaire 19.6 days before an allograft. Several positive psychological dispositions (i.e. mindfulness, optimism, and acceptance) and a negative psychological disposition (i.e. experiential avoidance) were assessed. Our dependent variables were mental health (i.e. happiness, depression, and anxiety) and QoL. Results: In the sample, 56.8% of patients were characterized by an impaired QoL and 56.9% and 21% had, respectively, anxiety and depression levels above the critical threshold (i.e. a score above seven on the Hospital Anxiety and Depression Scale). Anxiety, depression, and happiness were significantly related to the mental component of QoL, whereas physical QoL was only related to depression and happiness. Providing additional support for a complete state health approach, several positive and negative psychological dispositions (i.e. optimism, acceptance, and experiential avoidance) were robustly related to mental illness/wellness and QoL. Conclusions: These results highlight the importance of improving psychological health and QoL among HSCT patients prior to hospitalization by both promoting positive psychological and health factors and alleviating negative ones.